Characterization of spindle pole body duplication reveals a regulatory role for nuclear pore complexes - Rüthnick, Diana; Neuner, Annett; Dietrich, Franziska; Kirrmaier, Daniel; Engel, Ulrike; Knop, Michael; Schiebel, Elmar (The journal of cell biology, 2017)
The spindle pole body (SPB) of budding yeast duplicates once per cell cycle. In G1, the satellite, an SPB precursor, assembles next to the mother SPB (mSPB) on the cytoplasmic side of the nuclear envelope (NE). How the growing satellite subsequently inserts into the NE is an open question. To address this, we have uncoupled satellite growth from NE insertion. We show that the bridge structure that separates the mSPB from the satellite is a distance holder that prevents deleterious fusion of both structures. Binding of the γ-tubulin receptor Spc110 to the central plaque from within the nucleus is important for NE insertion of the new SPB. Moreover, we provide evidence that a nuclear pore complex associates with the duplicating SPB and helps to insert the SPB into the NE. After SPB insertion, membrane-associated proteins including the conserved Ndc1 encircle the SPB and retain it within the NE. Thus, uncoupling SPB growth from NE insertion unmasks functions of the duplication machinery.